Contrasting Journeys of Growth: A Study of Bildungsroman in Jenny Han's We'll Always Have Summer - Aurellia Salsabila; Y. B. Agung Prasaja (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the concept of Bildungsroman in Jenny Han's We'll Always Have Summer (2011). Bildungsroman is a literary genre that tells the story of a young person's development from youth into adulthood. This study focuses on two main characters, Belly Conklin and Jeremiah Fisher, analyzed through Female Bildungsroman theory and Anti-Bildungsroman theory respectively. Using qualitative research with a psychological approach, this study analyzes textual data comprising words, sentences, dialogues, and events in the novel. The findings reveal two contrasting paths of personal development. Belly's story exemplifies successful growth and maturity consistent with Female Bildungsroman, while Jeremiah's story illustrates incomplete personal development characteristic of Anti-Bildungsroman. Together, these characters demonstrate that true maturity comes from the ability to learn from experience and develop self-understanding. This study concludes that the Bildungsroman framework effectively explains contrasting processes of character development, revealing how emotional experiences, identity formation, and personal choices shape characters' journeys toward or away from maturity.